USE OF SMARTPHONE CAMERAS AS AN IMPLEMENTATION OF PRODUCT PHOTOGRAPHY FOR MSMEs - Dendi, Dendi (Journal of Public Relations and Digital Communication (JPRDC), 2024)
The purpose of this research is to understand how the use of smartphones is implemented in product photography by MSME actors in 26 Ilir, Palembang City. The type of research conducted is qualitative. Qualitative research is a strategy chosen by the researcher to observe or describe a phenomenon, gather information, and present the results of this study. Data collection techniques used to obtain data aligned with the research objectives include in-depth interviews, observation, and documentation. This research involved five informants from MSMEs in 26 Ilir, Palembang City. The findings include: MSME actors in 26 Ilir, Palembang City, use smartphones for product photography; however, one MSME actor does not implement product photography due to the lack of social media usage. The impact of photography on the promotions of MSMEs in 26 Ilir, Palembang City, on Instagram is significant, as the use of attractive and creative product photography enhances consumer appeal on each MSME's Instagram page in 26 Ilir, Palembang City.